Avaliação do potencial de inóculo de patógenos em sementes: sua relação com a qualidade fisiológica e quantificação do DNA fúngico por qPCR - Guimarães, Marina de Resende Faria (2016)
An important aspect in studies on the interaction of fungi and host seeds is the degree of colonization of the tissues by these agents. Depending on the intensity of this type of association, it is possible to estimate the consequences in farming environments. Having in mind what is already known in seed health and taking in consideration molecular methods for detection of Stenocarpella maydis, Stenocarpella macrospora in corn seeds, Colletotrichum gossypii var. cephalosporioides in cotton and Corynespora cassiicola in soybean seeds, the aim of this study was to evaluate the effect of different inoculum potentials of those pathogens on seeds, through the germination and electrical conductivity tests, and quantify the inoculum potentials, by real time PCR. The fungi isolates were inoculated on corn and cotton seeds in different inoculum potentials, represented by the exposition of the seeds to the fungal colonies for 0, 24, 48, 96 hours; and 0, 36, 108 and 144 hours for soybeans. The seeds were submitted to germination, electrical conductivity, health tests and qPCR. Based on the blotter test, there was a higher incidence of fungus in most pathosystems with the increasing inoculum potential. Except for corn seeds inoculated with S. maydis, the incidence was similar for all inoculum potentials. A decrease in germination percentage was observed in all species, with the increase in the inoculum potential; the same was observed in the degradation of the seeds membranes, with great loss of exudates with increasing inoculum potential. By qPCR test it was confirmed that the seeds with the greatest inoculum potential were most negatively affected, indicating that the damage occurred in the seeds due to the higher concentration of pathogens. Therefore, it was concluded that there is a close relationship between inoculum potential of pathogens, the amount of DNA and physiological performance of seeds infected with these agents.